The eastern horizon A regional perspective - Gorzelak, Grzegorz (2020)
Countries and regions in Central and Eastern Europe (CEE) have gone through several challenges. They went through totalitarian and authoritarian communist regimes, gained independence at the end of the 19th century, faced new economic and political challenges and rejoined Europe in a perspective of mutual development. As different as they may be, despite recent populist movements, the CEE countries have much in common and regional policies can help the "forgotten places" to explore their opportunities, supporting democracy, cohesion, and local economies in the European Union. Grzegorz Gorzelak is a professor of economics, specialising in regional and local development policies and strategy building. He has collaborated with the World Bank, the OECD, DG Regio of the European Commission, several agencies of the Polish and Ukrainian governments, as well as regional and local authorities. This is the fourteenth essay in the Big Ideas series created by the European Investment Bank.